Impact of Timing of Endoscopy on Mortality in Non-variceal Upper Gastrointestinal Bleeding: A Retrospective Cohort Study - Foroughian, Mahdi; Ravaghi, Ali; Habibzadeh, Seyed Reza; Goshayeshi, Ladan; Abbasi Shaye, Zahra; Ziaei, Maryam; Talebi Doluee, Morteza (Galen Medical Journal, 2025)
Background: Non-variceal upper gastrointestinal bleeding is a common problem worldwide. The purpose of this study was to investigate the relationship between the mortality rate of patients referred to the emergency room with non-variceal upper gastrointestinal bleeding and the time of therapeutic-diagnostic endoscopy. Materials and Methods: This study was a retrospective cohort observational study at Imam Reza Hospital in Mashhad, which was conducted in patients presenting with obvious symptoms of non-variceal acute gastrointestinal bleeding between April 2017 and March 2018. Underlying variables, endoscopic history, hemoglobin level, Glasgow – Blatchford score, blood pressure and the endoscopic result were extracted from patients’ records. Results: In this study, 189 patients (with an average age of 60.11 ± 17.59 years) were examined. 23 cases (12.16%) of death were recorded within 30 days. 26 people (13.75%) underwent emergency endoscopy within 0 to 6 hours of referral. Forty-four people (23.28%) underwent endoscopy within 6 to 12 hours and the rest (119 people, 62.96%) within 12 to 24 hours. There was no significant difference between deceased and recovered subjects in terms of various study variables, including Blatchford score, number of days hospitalized in the ward and intensive care unit, and the number of units of compressed red blood cells injected (P>0.05). Diabetes was significantly more prevalent in patients undergoing endoscopy <12 h compared to the >12 h (3.36% vs. 32.86%; P=0.001). adjusting for diabetes, the timing of endoscopy (within 12 hours vs. after 12 hours) was not significantly associated with mortality, with both crude (OR 1.25, 95% CI 0.63-2.49, P=0.523) and adjusted (OR 1.30, 95% CI 0.65-2.60, P=0.456) odds ratios. Conclusion: Our study showed no association between endoscopy time and mortality in patients with upper gastrointestinal bleeding; however, this finding should be confirmed in future studies in more controlled populations as a clinical trial.